The Study on Acute Subacute Toxicity and Anti-cancer Effect of K-herbal-acupuncture - Kwang-Ho, Kim; Ki-Rok, Kwon (Korean Pharmacopuncture Institute, 2003)
Objectives : The purpose of this study was to investigate Acute· Subacute Toxicity and Anti-cancer Effect of K-Herbal-acupuncture in mice and rats. Methods : Balb/c mice were injected intraperitoneally with K- herbal-acupuncture for LD50 and acute toxicity test. Sprague-Dawley rats were injected intraperitoneally with K-herbal-acupuncture for subacute toxicity test. K-Herbal-acupuncture was injected on abdomen of mice with S-180 cancer cell line. Result : 1. LD50 of K-Herbal-acupuncture was limited 4×10-3ml/kg～2×10-3ml/kg by the test. 2. In acute toxicity test, all of mice were down to the moving reflex, but the weight of mice was increased in treatment group, compared with the normal group. (p<0.05) 3. In acute toxicity test of serum biochemical values of mice, glucose was increased in treatment II group, total cholesterol was increased both treatments.(p<0.05) 4. In subacute toxicity test, the clinical signs of toxication was down to the moving reflex, but it is not severe like acute toxicity test, and observed weight loss at the treatments. 5. In subacute toxicity test, liver weight was decreased compared with the normal group. (p<0.05) 6. In subacute toxicity test of complete blood count test (CBC) of rat, HCT was decreased in treatments, compared with the normal group.(p<0.05) 7. In subacute toxicity test of serum biochemical values of rat, uric acid and triglyceride were decreased, and glucose was increased in treatment groups compared with the control group. (p<0.05) 8. Median survival time was increased about 45% in treatment groups compared with the control group.(p<0.05) 9. Natural killer cell activity was increased in B16F10 lung cancer model, but it was not in sarcoma-180 abdomen cancer. 10. In interleukin-2 productivity test, treatment groups didn't show significant change in lung cancer and abdomen cancer, compared with the normal group.(p<0.005) 11. In making an examination of metastatic cancer with the naked eye, melanoma metastasized in the Lung of C57BL/6 mice. The treated group showed more Melanoma than the control in the numbers and volume. Conclusion : According to the results, K-herbal-acupuncture need further study to know the function and effect in cancer.